2011
DOI: 10.1159/000331046
|View full text |Cite
|
Sign up to set email alerts
|

Dizziness in the Emergency Room: Diagnoses and Misdiagnoses

Abstract: Background: Dizziness is among the most frequent neurological chief complaints in emergency room (ER) patients. Although the majority of underlying disorders are benign, serious causes that require immediate in-hospital treatment may occur that are difficult to identify clinically. Methods: Retrospective study of 475 consecutive ER neurological consultations with dizziness as the chief complaint. Results: Of all ER dizziness patients, 73% were initially assigned to benign and 27% to serious diagnoses. The two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
5
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 44 publications
5
70
5
12
Order By: Relevance
“…A study that looked at the prevalence of misdiagnoses among dizzy patients found that the main diagnostic challenge lay in distinguishing vestibular neuritis from stroke [2]. For this purpose among AVS patients, the HINTS+ algorithm, which was rarely used in our study, may be of help [12].…”
Section: Discussionmentioning
confidence: 99%
“…A study that looked at the prevalence of misdiagnoses among dizzy patients found that the main diagnostic challenge lay in distinguishing vestibular neuritis from stroke [2]. For this purpose among AVS patients, the HINTS+ algorithm, which was rarely used in our study, may be of help [12].…”
Section: Discussionmentioning
confidence: 99%
“…B. peripher vestibulĂ€ren Ätiolo-gien neurologische Expertise beispielsweise durch Beurteilung eines Nystagmus erfordert [8]. Selbst in einer großen deutschen Notaufnahme musste in 6 % der FĂ€lle die initiale benige Ätiologie-vermutung zugunsten einer gravierenden Diagnose revidiert werden, wĂ€hrend umgekehrt in 23 % der FĂ€lle der Verdacht einer gravierenden Diagnose nicht bestĂ€-tigt werden konnte [9].…”
Section: Neurologische Expertise Bei Vieldeutigen Symptomenunclassified
“…Dizziness is among the most frequent symptoms in emergency room patients as demonstrated by Royl et al in 2011 [1]. The management must be fast and effective due to similarities to central causes and to the great discomfort it causes to the patients.…”
Section: Introductionmentioning
confidence: 99%